(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The article analyzes procedures for creation and staging of the play The Partenon Metophes, by Romeo Castellucci. Based on Judith Butler and Walter Benjamin, we analyze central topics for the work, such as: the artist’s use of images of war and violence that circulate in our daily lives; dialogue with aspects of the tragedy; the reference to the American artist Andy Warhol; the dissociation of the relationship between seeing and knowing that he proposes to his audience. Focusing on the formal choices of unframing, repetition of scenes and exposure of the bodies of the actors and actresses in this play, we seek to understand how the artist seeks a work in which the experiences of commotion and catharsis are suspended or displaced.